The analgesic power of pleasant touch in individuals with chronic pain: Recent findings and new insights - Fusaro, Martina; Bufacchi, Rory J.; Nicolardi, Valentina; Provenzano, Luca (Frontiers in Integrative Neuroscience, 2022)
This mini-review covers recent works on the study of pleasant touch in patients with chronic pain (CP) and its potential use as a treatment. While experiments have demonstrated that pleasant touch, through the activation of CT-afferents and the brain regions involved in its affective value, might reduce the unpleasantness and intensity of induced pain, the interaction between pleasant touch and CP remains under-examined. Some experiments show that CP might disrupt the positive aspects of receiving pleasant touch, while in other studies the perception of pleasantness is preserved. Moreover, only a few attempts have been made to test whether touch can have a modulatory effect on CP, but these results also remain inconclusive. Indeed, while one recent study demonstrated that CT-touch can diminish CP after a short stimulation, another study suggested that pleasant touch might not be sufficient. Future studies should further investigate the psychological and neural interplay between pleasant touch and CP. In the conclusion of this mini-review, we propose a new tool we have recently developed using immersive virtual reality (IVR).